Detecting patterns of vertebrate biodiversity across the multidimensional urban landscape. (3rd February 2022) - Alberti, Marina; Wang, Tianzhe
Abstract: Explicit characterisation of the complexity of urban landscapes is critical for understanding patterns of biodiversity and for detecting the underlying social and ecological processes that shape them. Urban environments exhibit variable heterogeneity and connectivity, influenced by different historical contingencies, that affect community assembly across scales. The multidimensional nature of urban disturbance and co‐occurrence of multiple stressors can cause synergistic effects leading to nonlinear responses in populations and communities. Yet, current research design of urban ecology and evolutionary studies typically relies on simple representation of the parameter space that can be observed. Sampling approaches apply simple urban gradients such as linear transects in space or comparisons of urban sites across the urban mosaic accounting for a few variables. This rarely considers multiple dimensions and scales of biodiversity, and proves to be inadequate to explain observed patterns. We apply a multidimensional approach that integrates distinctive social, ecological and built characteristics of urban landscapes, representing variations along dimensions of heterogeneity, connectivity and historical contingency. Measuring species richness and beta diversity across 100 US metropolitan areas at the city and 1‐km scales, we show that distinctive signatures of urban biodiversity can result from interactions between socioecological heterogeneity and connectivity, mediated by historical contingency. Abstract : Understanding complex interactions among the social and ecological determinants of community assembly in urban landscapes is critical to maintain biodiversity in a rapidly changing world. We develop a multidimensional approach that integrates distinctive social, ecological, built and biophysical characteristics of urban landscapes and show that distinctive signatures of urban biodiversity can be detected along dimensions of heterogeneity, connectivity and historical contingency.